The Effect of the Reading Aloud Strategy on Improving Reading Comprehension in Binjai State High School Students - Ismail, Ismail; Rezeki, Tri Indah; Purba, Azrina (Journal of Ecohumanism, 2024)
Reading comprehension of high school students in 21st century learning is one of the key skills in education that affects students' overall academic ability. Effective learning strategies in improving reading comprehension are an important focus in educational research. One of the strategies that has been discussed a lot is "Reading Aloud" or reading the text aloud. This study aims to explore the effectiveness of the Reading Aloud strategy in improving students' reading comprehension in 3 Binjai State High Schools: SMA Negeri 1, SMA Negeri 5, and SMA Negeri 7. This study is a quantitative research using Posttest-Only Design with Nonequivalent Groups. The number of samples in this study is 120 students spread across 3 State High Schools in Binjai City. The sampling procedure in this study uses Systematic Random Sampling. Data collection in this study uses a reading comprehension improvement test. This study uses the Independent Sample T-Test analysis technique with an increase effectiveness test using N-Gain. The results of this study show that there is an influence of the Reading Aloud strategy can increase students' reading comprehension with a significance value of 0.013. Furthermore, the results of this study show that the Reading Aloud strategy is quite effective in improving students' reading comprehension in the medium category with a gain value of 0.56 in the experimental group.